Maintaining cooperative sustainability: The mediation role of performance measurement systems - Rudiyanto, Rudiyanto; Munawar, Niknik Ahmad; Prayoga, Rahmat; Arini, Dewi Ulfah; Mufliha, Dewi Insani (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to identify an ideal information system to support cooperative organizations in enhancing their managerial performance and promoting long-term business sustainability. Research Methodology: Data were collected through distributed questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed hypotheses. Results: The findings confirm that Management Accounting Information Systems (MAIS) and Performance Measurement Systems (PMS) significantly and positively affect Managerial Performance (MP). PMS is shown to mediate the relationship between MAIS and MP. These results are expected to offer practical insights for cooperative managers in applying accounting principles and performance tools. Conclusions: This research reveals that quality and timely MAIS are vital for decision-making in cooperatives and SMEs. PMS plays a critical mediating role by reinforcing the positive impact of MAIS on MP. Limitations: The study is limited by the narrow scope of research, small sample size, and respondents with limited work experience. It also faces challenges in accounting for diverse member backgrounds. Future research should involve broader samples, more variables (e.g., budgeting, accountability), and improved methods.